DESIGN OF A CENTRIFUGAL COMPRESSOR FOR NATURAL GAS - Kurauchi, S. K.; Barbosa, J. R. (Revista de Engenharia Térmica, 2013)
This work presents the design of a centrifugal compressor for natural gas in three steps. The first step is the 1-D preliminary design heavily based on empirical data, only the design point was considered here. The second step is the flow analysis in the meridional plane. The last step is the CFD analysis to verify if the 1-D design methodology is adequate. The CFD simulations showed good agreement with the results obtained in the preliminary design, proving the importance of empirical data in the design of centrifugal compressors.